Peningkatan Pengetahuan Gizi Seimbang Sebagai Upaya Pencegahan Stunting Pada Ibu Hamil Dan Ibu Balita Melalui Pengenalan Pengolahan Makanan Sehat Di Desa Teratak Kecamatan Batukliang Utara - Indah Permata Sari; Anas Ikhlasul Amal; Dede Imelda Syarif; Ira Aisyah; Merly Yanti; Muhammad Zhafran Amin; Mustakim; Nur Nafisah; Rasidah Rizki; Rezki Triviananda; Yuniar Islamiati; Yusril Ihza Mahendra (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Stunting is a condition of failure to thrive in toddlers caused by chronic malnutrition cause the children are too short for their age. Teratak Village is one of the locus stunting areas in the province of West Nusa Tenggara has a high prevalence of stunting. One of the programs designed to overcome stunting in Teratak Village is introducing the manufacture of healthy food as a companion to staple foods for pregnant women and toddlers to fulfill balanced nutrition. In the introduction of this healthy food, Moringa leaves are process into pudding, so the result food product is more attractive. The introduction of processed Moringa leaf pudding was carried out in a stunting socialization activity held in Teratak Village. The socialization participants gave positive responses to the taste of the Moringa leaf pudding. The introduction of processed healthy foods from Moringa leaves was well received by the community.